Aplikasi Sosiologi Pengetahuan dalam Studi Hadis: Tijauan Kronologis-Historis terhadap Perumusan Ilmu Mukhtalif al-hadis asy-Syafi'i - Helmy, Muhammad Irfan (FENOMENA, 2020)
Enriching the perspective of the science of hadith can be done with the study of hadith which focuses on the sociological-historical dimension. One of studies that use a sociological-historical perspective is the science of Mukhtalif al-Hadith formulated by al-Shafi'i. The sociological approach to knowledge is used in this article to uncover the sociological dimension of the formation of mukhtalif al-hadith. The results of this approach reveal that the formulation of the science of mukhtalif al-hadith al-Shafi'i is started from the thoughts about the hadith during al-Shafi'i, especially those which are destructive to the position of hadith. In observing the sociology of knowledge, the science of mukhtalif al-Hadith formulation of al-Syafi'i must be open in order to create new method contributions in the meaning of mukhtalif hadiths.